Application of liquid biopsy for surgical management of pancreatic cancer. Issue 3 (12th February 2020) - Nagai, Minako; Sho, Masayuki; Akahori, Takahiro; Nakagawa, Kenji; Nakamura, Kota
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest forms of cancer. Although drug development over the past decade has gradually improved the prognosis of PDAC, the prognosis remains extremely poor. The predominant determinant of a poor prognosis is that patients are already at the advanced stage when they are diagnosed. Therefore, it is essential to detect early‐stage PDAC to ensure a good prognosis. However, in general, being asymptomatic at the early stage makes the detection of early‐stage PDAC very difficult. Recently, much attention has been focused on the utility of a liquid biopsy as a biomarker. Theoretically, early‐stage tumors can be detected even under asymptomatic conditions. A number of studies on liquid biopsies have been reported so far. Several biomarkers, including circulating tumor DNA (ctDNA), circulating tumor cells (CTCS), and exosomes, are used in liquid biopsies, with the potential to be applied to the clinical setting. Each biomarker is reported to have different utilities, such as the detection of early‐stage disease, the differential diagnosis of PDAC from other types of pancreatic tumors, the prediction of the prognosis or risk of recurrence, and monitoring the treatment response. In this review, we focus on ctDNA, CTCS, and exosomes as representative liquid biopsy biomarkers and describe the specific functions of each biomarker in the treatment of PDAC. Furthermore, we discuss the application of liquid biopsies, especially for the surgical management of PDAC. Abstract : Much attention has been focused on the utility of a liquid biopsy as a biomarker. We focus on ctDNA, CTCS, and exosomes as representative liquid biopsy biomarkers and describe the specific functions of each biomarker in the treatment of PDAC. Furthermore, we discuss the application of liquid biopsies, especially for the surgical management of PDAC.